MENGEMBANGKAN INDUSTRI BRIKET DENGAN MEMPERGUNAKAN MESIN PENGERING BRIKET ENERGI LISTRIK - PK Purwadi; Sudi Mungkasi; YB Lukiyanto (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2018)
In producing briquettes, the industry has problems in drying its briquettes. During this time briquette drying always involves solar energy. Drying with solar energy has weaknesses, namely (a) the ability to dry briquettes for a long time, cannot be accelerated (b) in the rainy season, solar energy is difficult to rely on, so the production capacity of briquettes per day decreases (c) to produce briquettes with large capacity, requiring a lot of raw material availability. These three weaknesses can be overcome if the briquette drying is done by using an electric energy briquette dryer. By using electric energy drying, the development of the briquette industry can be easily carried out. The purpose of this service implementation is to assist the human resources (HR) of the two briquette industry partners to increase, have complete knowledge of the electric energy briquette drying machine and use briquette drying machines to develop the industry. The results of the implementation of this service are (a) both partners know the briquette drying machine well and have the ability to make and function the electric energy briquette dryer (b) the two partners have a clear understanding to increase the briquette production capacity and determine all requirements and steps must be done to achieve production capacity as desired.